2016
DOI: 10.1016/j.ecoser.2016.07.007
|View full text |Cite
|
Sign up to set email alerts
|

Community-based groundwater and ecosystem restoration in semi-arid north Rajasthan (3): Evidence from remote sensing

Abstract: Community-based measures recharging groundwater in semi-arid India has historically underpinned rural socio-ecological resilience, though are declining through technological, policy and other changes. Nevertheless, exemplars of community action are achieving catchment regeneration, including in Alwar District (Rajasthan) since the mid-1980s. This study analysed satellite remote sensing (RS) data to detect trends in groundwater and linked ecosystem services. Data from Landsat satellite missions offered a long t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 26 publications
0
11
0
1
Order By: Relevance
“…Lower values and no significant positive correlations between NDVI LS and measured soil moisture at any depth or at any site were found. This suggests a rather limited role for the sensor in this context [33]. Compared to Sentinel-2, Landsat-8 has coarser spectral and spatial resolution (30 m), and this, in combination with the characteristics of vegetation at the sites, likely contributed to the lack of significant correlations with soil moisture.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lower values and no significant positive correlations between NDVI LS and measured soil moisture at any depth or at any site were found. This suggests a rather limited role for the sensor in this context [33]. Compared to Sentinel-2, Landsat-8 has coarser spectral and spatial resolution (30 m), and this, in combination with the characteristics of vegetation at the sites, likely contributed to the lack of significant correlations with soil moisture.…”
Section: Discussionmentioning
confidence: 99%
“…Research has suggested that the use of Landsat-8 at sub-regional scales to infer vegetation-soil moisture dynamics is nevertheless challenging due to the Operational Land Imager (OLI) sensor's spatial (30 m) and spectral resolution. Regardless, sensors with higher resolutions may be able to more accurately use NDVI to infer plant-water dynamics at these scales [33].…”
Section: Introductionmentioning
confidence: 99%
“…These indices are used to quantify chlorophyll, leaf water content, cellulose, lignin, and nitrogen, respectively [27]. Davies et al [75] used NDVI and MSI to assess temporal changes in vegetation cover, vigor, and moisture stress. Galletti et al [76] opted to use SAVI, an alternative to NDVI that reduces the effects of soil reflectance in sparsely vegetated landscapes, to assess moisture retention by agricultural terraces in Cyprus.…”
Section: Current Directions and Emerging Trends In The Remote Sensingmentioning
confidence: 99%
“…Water resources and hydrogeomorphology studies also benefit from the inclusion of remote sensing data. Remote sensing has been used to assess groundwater resources including monitor geomorphological environmental degradation caused by groundwater subsidence [22], changes in ecosystem services linked to groundwater [75], or modern climate and human impacts on hydrogeological processes in fluvial systems [58]. Remote sensing data with improved resolution can provide surrogate indicators of change in groundwater potential and thus support policy and local action in groundwater management priorities [75] or preservation of at-risk assets [22].…”
Section: Current Directions and Emerging Trends In The Remote Sensingmentioning
confidence: 99%
“…The starved flows of the Banas River, upon which the local community increasingly depends through increasingly mechanised extraction, compounds pressures in the river corridor created by direct habitat conversion. Elsewhere in Rajasthan and across India, restoration of community-based water harvesting, part of India's long and diverse tradition of water management for subsistence in arid conditions subject to only episodic rainfall, has proven a powerful stimulus for regenerating linked ecological and socio-economic wellbeing, with exemplar regions reversing cycles of decline and village abandonment (Jal Bhagirathi Foundation and Wells for India, 2010; Mahnot et al, 2012;Everard, 2015 andDavies et al, 2016;Wells for India, 2016). There are opportunities in the study site to invest in well-established rainwater harvesting techniques to alleviate pressures on water resources critical for people and wildlife and particularly given evidence of dwindling flows in the Banas river upon which there is increasing rural community dependency (Upadhyay and Rai, 2013), contributing to solutions to increase ecosystem service capacity in Amlidha for the simultaneous benefit of people and wildlife.…”
Section: Societal Characteristics and Changementioning
confidence: 99%